The Effect of Graded Running Protocols On Peak Oxygen Consumption and Intramuscular Oxygen Saturation - PELVAN, SERDAR ORKUN; AKBAŞ, SAVAŞ; ÇOTUK, HASAN BİROL (My University, 2024)
Aim: The aim of this investigation was to examine the impact of two different running protocols on peak oxygen consumption (VO2max) and regional intramuscular oxygen saturation (SmO2) levels in one highly trained runner. Methods: VO2 and SmO2 were measured simultaneously during a gradually ascending running protocol and a Bruce protocol. VO2 was measured by breath-by-breath spiroergometer gas analysis system (ZAN®, Germany), and SmO2 was measured from both gastrocnemius muscles using a wireless near-infrared spectroscopy device (BSXinsight®, USA). The correlation between VO2 and SmO2 data was determined by Pearson correlation coefficients over the test stage mean values. The change of VO2 and SmO2 within each stage was determined by firstdegree polynomials. Results: Peak VO2 in the Bruce protocol (4640 ml/min) was higher than peak VO2 in the running protocol (4390 ml/min), but no difference was observed in end-test SmO2 decreases. There were highly significant negative correlations between VO2 values and SmO2 values (r=- 0.960-0.990, p<0.001). SmO2 values measured in the right and left gastrocnemius muscle decreased similarly in both protocols (r=0.993, r=0.987, p<0.001). Conclusion: Central and peripheral physiological processes of oxygen consumption are not always congruent, and the test protocol exert an influence due to the complex interplay of physiological and biomechanical factors.

Amaç: Bu araştırmanın amacı, üst düzey antrenmanlı bir koşucuda, iki farklı koşu protokolünün zirve oksijen tüketimi (VO2max) ile bölgesel kas içi oksijen satürasyonu (SmO2) üzerindeki etkisini incelemektir. Yöntem: Kademeli artan koşu protokolü ve Bruce protokolü esnasında VO2 ve SmO2 eş zamanlı olarak ölçülmüştür. VO2, her nefeste spiroergometre gaz analiz sistemi (ZAN®, Almanya) ile ölçülürken SmO2, kablosuz yakın kızılötesi spektroskopi cihazı (BSXinsight®, ABD) kullanılarak her iki gastroknemius kasından ölçülmüştür. VO2 ve SmO2 verileri arasında ilişki, test kademe ortalamaları üzerinden Pearson korelasyon kat sayıları ile belirlenmiştir. Her bir kademe süresince VO2 ve SmO2 değişimi 1. derece polinomlarla belirlenmiştir. Bulgular: Bruce protokolünde zirve VO2 (4640 ml/dk) değeri koşu protokolü zirve VO2 (4390 ml/dk) değerine göre daha yüksek bulunmuştur, ancak test sonu SmO2 düşüşleri arasında fark gözlenmemiştir. VO2 değerleri ile SMO2 değerleri arasında negatif yönde çok yüksek düzeyde anlamlı ilişki mevcuttur (r=-0,960-0,990, p<0,001). Her iki protokolde sağ ve sol gastroknemius kasında ölçülen SmO2 değerleri benzer şekilde düşüş göstermiştir (r=0,993, r=0,987, p<0,001). Sonuç: Oksijen tüketiminin merkezi ve periferik fizyolojik süreçleri her zaman uyumlu değildir ve test protokolü, fizyolojik ve biyomekanik faktörlerin karmaşık etkileşimi nedeniyle bir etki oluşturur.
Kademeli Koşu Protokollerinin Tepe Oksijen Tüketimi ve Kas İçi Oksijen Doygunluğu Üzerindeki Etkisi
Keywords: Vo2Max; Yakın Kızılaltı Spektroskopi; Kas Oksijenlenmesi; MaxVo2; Near İnfrared Spectroscopy; Muscle oxygenation